Reporting Misconduct of a Coworker to Protect a Patient: A Comparison between Experienced Nurses and Nursing Students. (14th October 2014) - Mansbach, Abraham; Kushnir, Talma; Ziedenberg, Hana; Bachner, Yaacov G.
Abstract : Purpose . Whistleblowing is the reporting of illegal, immoral, or illegitimate practices to persons or organizations that may affect the action. The current study compares experienced nurses to nursing students regarding their willingness to blow the whistle to protect a patient's interests. Methods . 165 participants were divided into two groups: 82 undergraduate nursing students and 83 experienced nurses. Participants responded to two vignettes that described a colleague's and a manager's misconduct at work. Results . The nursing students perceived the severity of the misconduct significantly lower compared to the experienced nurses. The nursing students also ranked the internal and external whistleblowing indices higher than the nurses, but the differences did not reach statistical significance. For each of the examined internal and external indices, professional experience was found to be significant in multivariate regression analyses. Conclusions . Even though nursing students perceived the severity of the misconduct significantly lower than the experienced nurses, the students demonstrated a greater readiness to blow the whistle, both internally and externally. Recommendations for handling comparable situations are offered.